The practical guide to wedding planning - Haverly, Marie (Routledge, Taylor & Francis Group, 2022)
"This concise yet comprehensive guide offers highly practical insights and advice to those wanting to plan weddings as a career choice. Written by a highly experienced ex-wedding planner, this will be invaluable reading for those looking to enter or progress in the world of wedding planning, those already working in the industry, studying an events management programme, or perhaps looking for a career change"--